The meanings, risk factors and consequences of religious extremism: The perceptions of Islamic education teachers from Israel. (16th July 2022) - Saada, Najwan
Abstract: This multiple case study examines the attitudes of 14 Islamic education teachers from Israel towards the meaning, causes and consequences of religious extremism among students in their Arab and Muslim‐majority middle and high schools. These teachers define religious extremism as belief in absolute religious truth, inflexibility in religious interpretation, or strict adherence to Islamic teachings. In addition, the teachers distinguish the personal (adolescence, family problems and psychosocial needs), religious (unquestioned following of extremist imams or religion scholars; adopting of selective, literal and decontextualised readings of the religious text; influence of partisan teachers) and socio‐political factors (students' feelings of fear and anger towards Israel and its unjust and oppressive role in the Palestinian–Israeli conflict) that push students towards religious extremism. Religious extremism, the teachers conclude, may lead to hatred or violence against followers of other religions, antagonism between Muslims and Jews in Israel, increased Islamophobia in Western societies, the rejection of Islam, the oppression of female students and reduced student achievement and diminished future prospects.